2014
DOI: 10.15288/jsads.2014.s17.50
|View full text |Cite
|
Sign up to set email alerts
|

Seventy-Five Years of Comorbidity Research

Abstract: ABSTRACT. Objective: As part of the 75th anniversary edition of the Journal of Studies on Alcohol and Drugs, this article reviews research on the relationship between mental disorders and substance use disorders ("comorbidity") from 1940-the journal's inception-to the present. Method: First, a survey of the titles and abstracts of all articles published in the journal was used to identify those articles pertaining to comorbidity. Seminal and representative works from this set of articles and a limited selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…However, recent and historic data have shown that these numbers were significantly higher in individuals diagnosed with diseases such as major depressive disorder or trauma and stressor-related disorders and these populations tended to be less responsive to treatment (Grant et al, 2016; Kranzler and Rosenthal, 2003). These findings are consistent with a large body of literature suggesting a high degree of comorbidity between AUD and a wide range of affective disorders (Brenhouse and Andersen, 2011; Brodie et al, 1999; Buckley, 2006; Buckley and Brown, 2006; Kessler, 2004; Kushner, 2014). …”
supporting
confidence: 90%
“…However, recent and historic data have shown that these numbers were significantly higher in individuals diagnosed with diseases such as major depressive disorder or trauma and stressor-related disorders and these populations tended to be less responsive to treatment (Grant et al, 2016; Kranzler and Rosenthal, 2003). These findings are consistent with a large body of literature suggesting a high degree of comorbidity between AUD and a wide range of affective disorders (Brenhouse and Andersen, 2011; Brodie et al, 1999; Buckley, 2006; Buckley and Brown, 2006; Kessler, 2004; Kushner, 2014). …”
supporting
confidence: 90%
“…Consistent with this, DTC has been associated with life stressors such as poverty and work difficulties (c.f., Kushner, 2014) in the absence of AnxD. Further, affect regulation training (ART) has been shown to significantly improve abstinence rates among AUD treatment outpatients who endorse DTC in the absence of an AnxD (Stasiewicz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the bulk of psychopathology research is still conducted on specific manifestations of comorbidity, or on specific disorders in isolation, as if they are etiologically and pathophysiologically unique (Caspi et al, 2014; Lahey et al, 2011). If this were the case, every possible disorder pairing would also be unique, and would require its own comorbidity model (Kushner, 2014). However, analyses of the correlations among DSM disorders have taught us that, empirically, these disorders are best conceptualized as indicators of the IE spectra.…”
Section: The Case For Moving Beyond Comorbidity As a Focus In Researchmentioning
confidence: 99%